Determination of the Cadmium, Chromium, Nickel, Lead and Cobalt in Selected vegetables and their transfer and translocation factor (International Journal of Food and Nutritional Sciences, 2022)
The heavy metals pollution is one of the problems that arise because of the increased uses of fertilizers and other chemicals to fulfil the higher demands of food production for human consumption. In the present study different methods, for assessment of the heavy metals concentration in the human body contributed by contaminated vegetables, are discussed. The concentration of Cr, Co, Cd, Pb and Ni in the soils was ranged from 0.11-0.231, 5.151-6.662, 3.2-4.32, 7.19-8.79, 7.16-7.72mg/kg with mean value (p = 0.05) of 0.146 ± 0.046, 5.731±0.527, 3.803±0.503, 7.770±0.504, 7.435±0.504mg/kg, respectively. The contamination, sources and bioaccumulation of the heavy metals i.e. Cr, Cu, Pb, Cd and Ni in the vegetables are described.